Mutations causing Lopes-Maciel-Rodan syndrome are huntingtin hypomorphs. Issue 3 (11th January 2021) - Jung, Roy; Lee, Yejin; Barker, Douglas; Correia, Kevin; Shin, Baehyun; Loupe, Jacob; Collins, Ryan L; Lucente, Diane; Ruliera, Jayla; Gillis, Tammy; Mysore, Jayalakshmi S; Rodan, Lance; et al.
Abstract: Huntington's disease pathogenesis involves a genetic gain-of-function toxicity mechanism triggered by the expanded HTT CAG repeat. Current therapeutic efforts aim to suppress expression of total or mutant huntingtin, though the relationship of huntingtin's normal activities to the gain-of-function mechanism and what the effects of huntingtin-lowering might be are unclear. Here, we have re-investigated a rare family segregating two presumed HTT loss-of-function (LoF) variants associated with the developmental disorder, Lopes-Maciel-Rodan syndrome (LOMARS), using whole-genome sequencing of DNA from cell lines, in conjunction with analysis of mRNA and protein expression. Our findings correct the muddled annotation of these HTT variants, reaffirm they are the genetic cause of the LOMARS phenotype and demonstrate that each variant is a huntingtin hypomorphic mutation. The NM_002111.8: c.4469+1G>A splice donor variant results in aberrant (exon 34) splicing and severely reduced mRNA, whereas, surprisingly, the NM_002111.8: c.8157T>A NP_002102.4: Phe2719Leu missense variant results in abnormally rapid turnover of the Leu2719 huntingtin protein. Thus, although rare and subject to an as yet unknown LoF intolerance at the population level, bona fide HTT LoF variants can be transmitted by normal individuals leading to severe consequences in compound heterozygotes due to huntingtin deficiency.